2012
DOI: 10.1016/j.ympev.2011.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Giant taro and its relatives: A phylogeny of the large genus Alocasia (Araceae) sheds light on Miocene floristic exchange in the Malesian region

Abstract: Alocasia comprises over 113 species of rainforest understorey plants in Southeast Asia, the Malesian region, and Australia. Several species, including giant taro, Alocasia macrorrhizos, and Chinese taro, Alocasia cucullata, are important food plants or ornamentals. We investigated the biogeography of this genus using plastid and nuclear DNA sequences (5200 nucleotides) from 78 accessions representing 71 species, plus 25 species representing 16 genera of the Pistia clade to which Alocasia belongs. Divergence ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
86
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(91 citation statements)
references
References 46 publications
4
86
0
1
Order By: Relevance
“…In both analyses, the order of the genera and species are in agreement with those in the previous studies [12][13][14][15][16].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In both analyses, the order of the genera and species are in agreement with those in the previous studies [12][13][14][15][16].…”
Section: Discussionsupporting
confidence: 90%
“…very numerous) found in those of Colocasia [3-5, 9, 11]. Due to the morphological divergence of A. rivularis, we have used molecular data to ascertain its phylogenetic relationship to known species of Alocasia, especially those of the Cuprea Group, and other genera of the tribe Colocasieae, applying the methods employed similarly in previous phylogenetic studies of the Araceae [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…While the barrier to crossing Wallace's line has proved to be a hindrance for the dispersal in many faunal groups, it is less so among plants (Van Welzen et al, 2011). Other examples of an inferred origin of flora in Borneo and subsequent dispersal across Wallace's line during the Miocene include Rhododendronsection Vireya (Ericaceae) (Brown et al, 2006;Webb and Ree, 2012), Alocasia (Araceae) (Nauheimer et al, 2012) and Begonia (Thomas et al, 2012). Finally, the dispersal of two taxa native to the Western Ghats of India may be the result of overland or overwater dispersal.…”
Section: Resultsmentioning
confidence: 99%
“…Within Southeast Asia, certain regions may have higher rates of endemism and diversification. For example, de Bruyn et al (2014) recently identified Borneo and Indochina as 'evolutionary hotspots' in a phylogenetic meta-analysis of both flora and fauna, and several studies cite Borneo as the centre of diversification for multiple taxa (Nauheimer et al, 2012;Webb and Ree, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The potential of dust-like seeds for rare longer distance dispersals by wind might be greater compared with other plants with propagules locally dispersed by animals (e.g. Araceae 39 ). Indeed, detailed studies on epiphyte orchid seed dispersal and gene flow provide evidence for the rarely long distance exchange of orchid propagules between geographical areas 4042 .…”
Section: Introductionmentioning
confidence: 99%